Efficacy of interpersonal psychotherapy in mainland China: a systematic review and meta-analysis - Luhan Tang; Fangzhong Xu; Ge Yu; Chong Li; Sijin Wen; Wanhong Zheng (Frontiers in Psychiatry, 2023)
ObjectiveInterpersonal Psychotherapy (IPT) is an evidence-based therapy. There have been increasing demand and training opportunities of IPT in China. Reviewing current evidence on its use in Chinese patients can help us understand the applicability of IPT in China and identify knowledge gaps to encourage and better future research in this field.MethodWe did a comprehensive search of three major electronic databases: PubMed (English), Chinese National Knowledge Infrastructure (CNKI) and WanFang Data (Chinese). We examined overall study design, outcome measures, data analyses and other parameters. We only selected articles of Randomized Clinical Trials (RCT) for this review. All study findings were grouped and summarized per psychiatric diagnoses. The meta-analysis and forest plots were performed whereas studies could be combined.ResultsAfter a full text review of 132 articles, 40 were selected for the final review. Comparing with control groups, evidences supported the efficacy of IPT in Chinese patients with Major Depressive Disorder (MDD), Postpartum depression, Generalized Anxiety Disorder (GAD), Social Anxiety Disorder, Post Stress Traumatic Disorder (PTSD), and Post-psychotic Depression. It was also beneficial to college students and Chinese first-time mothers. Meta-analysis using a random-effects model consistently yielded significant score differences between the IPT and control groups (p < 0.0001) on MDD.ConclusionThis systematic review has identified the current best evidence for IPT efficacy in Chinese population. The findings support IPT as an effective treatment in Chinese with certain psychiatric conditions, consistent with those from many other studies throughout the world.